Existence of stationary turbulent flows with variable positive vortex intensity. (December 2017) - De Marchis, F.; Ricciardi, T.
Abstract: We prove the existence of stationary turbulent flows with arbitrary positive vortex circulation on non-simply connected domains. Our construction yields solutions for all real values of the inverse temperature with the exception of a quantized set, for which blow-up phenomena may occur. Our results complete the analysis initiated in Ricciardi and Zecca (2016).